Gramatika u rječniku na primjeru valentnosti - Matijević, Maja (SlavVaria, 2022)
Grammar in a dictionary on the example of word valency. This paper analyses complements in general monolingual dictionaries of the Croatian language. The inclusion of complements in a dictionary definition or dictionary articles is discussed, as well as the means of emphasizing the complement. After the part about word valency in linguistics (which finds the complement as one of the most important concepts) and the part about specialized dictionaries that directly or indirectly deal with valency, the work also analyses the lexicographic compilation of verbs of different valency in four general monolingual dictionaries of the Croatian language: Rječnik hrvatskoga jezika (RHJ), Hrvatski jezični portal (HJP), Veliki rječnik hrvatskoga standardnog jezika (VRH) and Mrežnik. The paper also brings a proposal for the lexicographic description of chosen verbs.